GRAIKIŠKASIS FILOSOFIJOS MITAS. - Saulius, Tomas (Problems / Problemos, 2008)
In the article, the possibility of the "non-technical" interpretation of Greek philosophy is discussed (in other words, we try to find the point of view opposite to that which Heidegger describes as the "technical" aspect of the interpretation of thought). From the "non-technical" point of view, philosophy is conceived essentially as a discourse, and its meaning and value do not depend on the external circumstances of practical application. The main assumption is that Greek philosophy inherits its primordial forms of self-reflection from the previous tradition of Greek literature. It becomes obvious when the new ideal of philosopher (i.e. "wisdom seeker") is analysed in the context of so-called "Greek wisdom".